Analysis of Legal Protection for Consumers in PT Muda Kaya Mendunia - Pahira, Siti Hapsah (Devotion : Journal of Research and Community Service, 2023)
PT Muda Kaya Mendunia is the holding company of Syntax Corporation which is engaged in educational services, scientific publications and information technology services which has been established since 2012. In digital business activities and digital service products offered by PT Muda Kaya Mendunia will have legal consequences against legal events between the company and consumers and consumer digital copyright protection when using the services of the company. The study aims to analyze the legal protection for cosumers in PT Muda Kaya Mendunia. The type of legal research that is carried out in a normative juridical manner is normative juridical where law is conceptualized as what is written in laws and regulations. Consumers in this case must be given a variety of special protections which are very vulnerable to various possibilities that will harm the consumers themselves from business actors who do not have good intentions in making buying and selling transactions online. Online transactions for both business actors and consumers must have good intentions from the start.